2019
DOI: 10.1016/j.cytogfr.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The imprinted gene Delta like non-canonical Notch ligand 1 (Dlk1) is conserved in mammals, and serves a growth modulatory role during tissue development and regeneration through Notch dependent and independent mechanisms

Abstract: The imprinted gene Delta like non-canonical Notch ligand 1 (Dlk1) is conserved in mammals, and serves a growth modulatory role during tissue development and regeneration through Notch dependent and independent mechanisms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 148 publications
2
36
1
Order By: Relevance
“…The inhibitory role of DLK1 and DLK2 proteins on NOTCH activation and signaling [8,[17][18][19][20][21][22]35] has been confirmed in many works of the scientific community [4,17,22,23,32,35,37,[96][97][98][99][100][101][102]. Recently, we observed that both DLK proteins inhibit each of the four NOTCH receptors' activities [18,19].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The inhibitory role of DLK1 and DLK2 proteins on NOTCH activation and signaling [8,[17][18][19][20][21][22]35] has been confirmed in many works of the scientific community [4,17,22,23,32,35,37,[96][97][98][99][100][101][102]. Recently, we observed that both DLK proteins inhibit each of the four NOTCH receptors' activities [18,19].…”
Section: Discussionmentioning
confidence: 71%
“…Recently, we observed that both DLK proteins inhibit each of the four NOTCH receptors' activities [18,19]. However, some authors have also reported that the DLK1 protein does not affect NOTCH signaling [37,[103][104][105][106], or even that it activates NOTCH signaling [25,91,[107][108][109]. Together with the existence of different DLK1 protein and probably DLK2 protein isoforms, self-and cross-interactions previously reported [22,110,111] could explain some of the contradictory effects reported for DLK proteins on NOTCH activation and signaling.…”
Section: Discussionmentioning
confidence: 86%
“…In this study, we observed cell type and time-specific expression of Dlk1 during muscle regeneration processes. Because Dlk1 expression is detected in proliferative hepatoblasts from the fetal liver [21,22] and in cancer cells [23,24], Dlk1 expression may also reflect the proliferative ability of mesenchymal progenitors. However, we observed that suppression of Dlk1 in mesenchymal progenitors did not affect the process of muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…While many functions of DLK1 appear related to its potential regulation of Notch signaling [10], other studies have found no evidence of Notch dependency for DLK1 [11], suggesting that the role of DLK1 can vary. Signaling from DLK1 can involve ADAM17-mediated release of its extracellular domain [12,13], with best-described consequences in inhibition of adipocyte differentiation. Mechanisms involve activation of the MEK/ERK pathway and Sox9 [14][15][16].…”
Section: Introductionmentioning
confidence: 99%